Thermal ageing on the microstructure and mechanical properties of Al–Cu–Mg alloy/bagasse ash particulate composites - V.S. Aigbodion (Journal of King Saud University: Engineering Sciences, 2014)
Thermal ageing on the microstructure and mechanical properties of Al–Cu–Mg alloy/bagasse ash(BAp) particulate composites was investigated. The composites were produced by a double stir-casting method by varying bagasse ash from 2 to 10 wt.%. After casting the samples were solution heat-treated at a temperature of 500 °C in an electrically heated furnace, soaked for 3 h at this temperature and then rapidly quenched in water and thermal aged at temperatures of 100, 200 and 300 °C. The ageing characteristics of these grades of composites were evaluated using scanning electron microscopy (SEM), hardness and tensile test samples obtained from solution heat-treated composites samples subjected to the temperature conditions mentioned above. The results show that the uniform distribution of the bagasse ash particles in the microstructure of both the as-cast and age-hardened Al–Cu–Mg/BAp composites is the major factor responsible for the improvement in mechanical properties. The presence of the bagasse ash particles in the matrix alloy results in a much smaller grain size in the cast composites compared to the matrix alloy. The addition of bagasse ash particles to Al–Cu–Mg (A2009) does not alter the thermal ageing sequence, but it alters certain aspects of the precipitation reaction. Although thermal ageing is accelerated in the composites the presence of bagasse ash particles in A2009 reduces the peak temperatures.